Proceedings of the URECA@NTU 2009-2010 - Students of URECA Programme (2024)
Proceedings of the URECA@NTU 2009-10 is a compilation of selected URECA and FYP-URECA research papers, submitted by the URECA students of 2009-10, and under the supervision of their respective URECA professors.